Android-Based Tourism and Culture Information System in Bantul Regency - Yanu Wikanandhi; Putri, Puji Handayani; Wahana, Aditya; Mohd Nawi, Mohd Nasrun (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2024)
Information systems are a combination of information technology and human activities that use technology to support operations and management. Tourism is a travel activity carried out by a person or group of people to an interesting place. One of the famous tourist and cultural attractions in Indonesia is Yogyakarta, especially Bantul Regency, which has very rich and diverse tourism and cultural potential. Limited access to information is a major obstacle for tourists and local people who want to explore Bantul Regency. To overcome this problem, a Tourism and Cultural Information System is needed that can facilitate visitors and the public in accessing information easily, accurately, and up to date. The benefits of the system are that the information presented in the application helps in efforts to preserve and promote local tourism and culture. and tourists can plan their trips well, including travel routes to tourist attractions and culture. Data collection methods by conducting observations, interviews, literature studies and research methods using the Waterfall method. The results of the system testing run well and the expected appearance and results are as expected.